Adaptasi Alat Ukur Revised - Suicide Ideation Scale (R-SIS) - Michelle Neivi Artissy; Ahmad Gimmy Pratama (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT: ADAPTATION OF REVISED-SUICIDE IDEATION SCALE (R-SIS) INSTRUMENTSuicide is the second leading cause of death for college students in the world. Suicide is influenced by various factors, such as negative behaviour, feelings, social and economic conditions. This study aims to adapt the Revised - Suicide Ideation Scale (R-SIS) from Rudd (1989) as a short screening instrument consisting of 10 items. This instrument is divided into two dimensions, resolved plans and preparations; and suicidal ideation. The output of this instrument measures the presence or absence of suicidal ideation in an individual and how serious the suicidal ideation, if any, is. The participants in this study were 106 students consisting of 30 men and 76 women. This study is a quantitative research that uses non-experimental quantitative methods. The results of Cronbach's Alpha on both dimensions and on the overall numerical measurement tools are very good, and show the reliability of this measuring instrument is acceptable. The results of the CFA calculation indicate a good-fit model, which internally supports the validity of the instrument in measuring Suicide Ideation. From these results, this measuring instrument can be declared internally supporting the validity of the instrumen. Thus, hopefully this instrument can help in capturing individual with suicide risk, especially college students for further treatment. Keywords: Suicide Ideation, College Students, Adaptation, Instrument Kasus bunuh diri merupakan salah satu penyebab kematian terbesar kedua pada mahasiswa di dunia. Bunuh diri dipengaruhi oleh berbagai faktor, seperti perilaku, perasaan negatif, serta kondisi sosial dan ekomi. Penelitian ini bertujuan untuk mengadaptasi alat ukur Revised Suicide Ideation Scale (R-SIS) dari Rudd (1989) sebagai instrumen skrining singkat yang terdiri dari 10 item. Instrumen ini terbagi dalam dua dimensi, resolved plans and preparations; dan suicidal desires. Keluaran dari instrumen ini mengukur akan ada atau tidak adanya ide bunuh diri pada suatu individu dan seberapa serius ide bunuh diri tersebut jika ada. Partisipan yang terlibat dalam penelitian ini sejumlah 106 mahasiswa yang terdiri dari 30 orang laki-laki dan 76 orang perempuan. Penelitian ini merupakan studi kuantitatif yang menggunakan metode kuantitatif non-eksperimental. Hasil cronbach alpha pada kedua dimensi dan pada keseluruhan alat ukur menunjukkan angka yang sangat baik, dan mengindikasikan reliabilitas alat ukur ini dapat diterima. Hasil penghitungan CFA mengindikasikan good fit dari model, yang secara internal mendukung validitas intrumen dalam mengukur Ide Bunuh Diri. Dari hasil tersebut, dapat disimpulkan bahwa alat ukur ini dapat dinyatakan valid secara konstruk internal. Sehingga, diharapkan dapat membantu dalam menjaring individu berisiko, utamanya pada mahasiswa utnuk diberikan penanganan lebih lanjut. Kata kunci : Ide Bunuh Diri, Mahasiswa, Adaptasi, Alat Ukur